Modelling and validation of a gas‐solid fluidized bed using advanced measurement techniques. (14th April 2021) - Uribe, Sebastián; Taofeeq, Haidar; Al‐Dahhan, Muthanna
Abstract: With a Euler‐two‐phase (E2P) approach, through computational fluid dynamics (CFD) techniques, a mathematical model for the prediction of the local hydrodynamic behaviour of a gas‐solid fluidized bed was implemented. Simulations are conducted for a fluidized bed of 0.14 m internal diameter packed with Gerdart B glass beads particles, with an average diameter of 365 μm, at dimensionless inlet velocities ranging from V β 0 V mf = 1.6 − 2.14 . The implemented model considers the multiphase and multiscale interactions through the inclusion of three sub‐models, which allows the model to have a broad range of applicability. Predictions were compared against experimental measurements reported on previous contributions for validation purposes. The experimental study was conducted by implementing advanced measurement techniques, such as a differential pressure transducer, and an optical fibre probe for simultaneous measurement of solids holdup and velocity, developed at the Multiphase Flow and Reactors Engineering and Applications Laboratory (mFReal). Local radial solids holdup, solids velocity, and pressure drop profiles were experimentally determined. Results show that the implemented model possesses a high predictive quality, predicting pressure drops with an average absolute relative error (AARE) between 8.6%–11.3%; solids holdup with a root mean squared deviation (RMSD) under 5%; and solids velocity with a RMSD under 22%.